حسابات نظرية لحاصل ترذيذ سطح البريليوم بواسطة حزمة ايونات بلازما الديوتيريوم - A . Jawad , Dr. Enas . (مجلة كلية التربية, 2020)
Extended calculations for sputtering yield through bombed Beryllium – target by Deuterium ions plasma are accomplished .Accounts include changing the input parameters: the energy of Deuterium ions plasma, the hit target angle of Beryllium target, thickness of the Beryllium target layer, The program TRIM is used to accomplish these calculations. Results show that sputtering yield is directly dependent on these parameters. It can change the incident angle of Deuterium ions and energy lead to a significant change in Sputtering yield . On the other hand, the sputtering yields are highly affected by changing target width at fixed ion parameters.